The Investigation of Significant Leptospirosis Hotspots during the Initial COVID-19 Pandemic in the City of Jakarta, Indonesia - Andre Yunianto; Dian Perwitasari; Dasuki Dasuki; Pandji Wibawa Dhewantara (Indian Journal of Forensic Medicine & Toxicology, 2022)
Leptospirosis is a common bacterial infection caused by pathogenic Leptospira spp.in tropical region, including inIndonesia. During the first year of COVID-19 pandemic, Jakarta reported a significant increase in leptospirosis cases.A study was conducted to analyze the distribution of leptospirosis and to identify hotspots of the leptospirosis.Leptospirosis notifications for the period of January to December 2020 were collected from the online surveillancedatabase provided by the Provincial Health Office of Jakarta. Global and local spatial clustering at the villagelevel across Jakarta was examined using Moran’s I and local indicators for spatial association (LISA). In 2020,total of 207 people infected by Leptospira spp. The highest number was recorded in January (n=142), accountingfor 68.5% of the total reports over the period studied. The incidence was geographically dissimilar at village-levelwith the highest rates was observed in the west of the city. Moran’s I analysis demonstrates that leptospirosisincidence was significantly clustered (I = 0.191, p-value = 0.001). Total of 19 high-risk clusters in 9 sub-districtswere identified and approximately 891,202 people were at higher risk of leptospirosis during the year of 2020. Thefindings suggest needs an improved disease surveillance to support spatially targeted interventions to controlleptospirosis transmission.